Economics - Colander, David C. (Boston, Mass. : Irwin/McGraw-Hill, 1998)
Thinking like an economist. Macroeconomics. Macroeconomic models: the basics. Traditional macro policy debates. Structural macro policy debates. Microeconomics.
Keywords: Economics; Economics